EVALUATION OF THE INFLUENCE OF STRUCTURAL PARAMETERS ON THE CHARACTERISTICS OF ANTI-ROLL BARS IN TRUCKS BY USING FINITE ELEMENT METHOD - Tat Thang, Pham; Manh Quan, Tran; Trong Tu, Do; Van Dung, Ngo; Van Tan, Vu (Journal of Applied Engineering Science, 2025)
The anti-roll bar is a critical component of the automotive suspension system, designed to improve vehicle stability during cornering or when uneven road surfaces induce load transfer between the wheels at an axle. This paper focuses on evaluating the characteristic changes of the anti-roll bar when modifying structural parameters and the positioning of bushings by using the Finite Element Method (FEM) by using HyperMesh software. Firstly, the anti-roll bar's dimensions were measured based on a truck anti-roll bar model, then a 3D model was created in Catia, followed by simulation and analysis in HyperMesh software. The simulation results were visualized using HyperView software. To examine the influence of structural parameters on the anti-roll bar's characteristics, this study concentrates on varying diameter sizes and different distances between rubber bushings. The results indicated significant changes in the relative displacement between the two poles of the bar and its stress distribution when the design parameters were altered. From these results, this study also evaluated the roll stiffness of the bar for trucks within a range of 10,000-50,000 Nm/rad. This research serves as a foundation for optimizing anti-roll bar designs, aiming for shape optimization and weight reduction while maintaining stiffness and durability, thereby enhancing vehicle safety under various operating conditions.
Keywords: anti-roll bar, roll stiffness, finite element method, hypermesh software, hyperview software, truck